Relevance of Nigerian Libraries in the Dissemination of Information in Post COVID–19 Era - Ofodu , Patricia Ngozi; Chime , Augustina Chinyere; Ekwueme , Loveth Ogoegbunam (Communicate: Journal of Library and Information Science, 2023)
This study aims at investigating the relevance of library services in dissemination of information during the COVID-19 Pandemic in Nigeria. There were changes in mode of teaching and learning, libraries also changed too to meet up with online provision and dissemination of information resources for students. The work captured the overview of the infection, COVID-19 as a global illness that started from Wuhan, China, the symptoms of the infection, how the virus can likely to be spread on a close contact with the victim or on any infected object. It also explained on how to prevent the spread of the infection like: washing hands regularly, maintain social distancing and strategies on how to curb the high risk of spread of the infection. This study shows how the virus got to Nigeria, which led to the closure of all social gathering and the alarming closure of schools, quarantine all students at home. The author discussed on the e-learning and libraries amidst pandemic, how possible they were able to exist. It also discussed some impacts of e-learning in academic libraries. The online provision of resources and services relevance to academic pursuit was also discussed. Relevance of library and its services, such as mobile learning, blogs, wikis were captured.